(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Harapan TS, Nurainas, Syamsuardi, Taufiq A. 2022. Identifying the potential geographic distribution for Castanopsis argentea and Castanopsis tungurrut (Family: Fagaceae) in the Sumatra Conservation Area Network, Indonesia. Biodiversitas 23: 1726-1733. Recently, Castanopsis argentea (Blume) A.DC. and Castanopsis tungurrut (Blume) A.DC. have been listed as endangered species by the International Union for the Conservation of Nature (IUCN). For conservation planning, it is important to know the full distribution of species. This study aimed to predict the potential distribution of C. argentea and C. tungurrut using MaxEnt, and understand key factors responsible for the distribution of these species. A total of 53 occurrences and six environmental variables were used to model their distribution. The AUC values of C. argentea and C. tungurrut were 0.86 and 0.91, respectively, and the models suggest the distribution of both species is mainly influenced by elevation, and temperature seasonality for C. tungurrut. The predicted distributions of the species are in the mountains of the western part of Sumatra, and their range includes 12 conservation areas that have highly suitable habitats for both species. After generating the MaxEnt prediction map, we conducted field validation to validate the model predictions. Field surveys in two predicted areas showed that the predicted distribution maps accurately estimated the distribution of C. argentea and C. tungurrut at those localities.